The Effectiveness of Group Counseling with Cognitive Restructuring Techniques to Increase Self-Confidence in Victims of Body Shaming in Batu Rancing Village - Erta Dwi Junianti; Suryati, Suryati; Hartika Utami Fitri (al-Afkar, Journal For Islamic Studies, 2025)
In today's modern era, especially with the development of technology and the rise of social media, many individuals are increasingly exposed to standards of beauty or ideal body shape, which are often unrealistic. One of the negative impacts of this phenomenon is the increasing incidence of body shaming, which is the act of shaming or criticizing people based on their physical appearance, such as body shape, weight, skin color, or other physical characteristics. Body shaming can happen anytime and anywhere, it can also be in various environments, both on social media, school, friends, and family. According to research conducted by Sahrina, body shaming has a negative impact on victims which can cause victims to experience decreased physical health and insomnia. In psychological explanation, people who are victims of body shaming can trigger depression, excessive anxiety and have thoughts of committing suicide. [1] It is undeniable that this act of body shaming can make victims blame themselves and punish themselves. When someone has become a victim of this body shaming treatment, they will tend to feel ashamed. Just like someone gets comments because their body looks fat, they will try to diet to become thin.